Carbon markets as regulation strategy: States, non-state market actors and public-private climate governance - Shash, Nouran (AUC Knowledge Fountain, 2015)
The thesis looks at whether the development of carbon markets as a key policy instrument to address climate change can be explained by the participation of non-state private market actors in decision-making processes at the institutional level. It looks at the underlying interests and stakes that both states and private non-state market actors have had in carbon trading, the role that states and businesses play in these markets and the implications that the adoption of this instrument has had, in terms of controversies regarding accountability, transparency and justice issues. Through investigating the role of one major private carbon market actor, BP, in policymaking processes, this study provides an example of how corporate interests influenced policy at the institutional level. The main hypothesis is that private non-state market actors influenced state policy in terms of adopting carbon markets designed to benefit and to prevent harm to corporate interests. This is done through mechanisms in which states acted to provide the conditions for effective market conduct, leaving it to market actors to implement the expected results according to their own standards with minimum state control. Market actors, on the other hand, expected states to provide a strong legal framework as well as the political legitimation necessary for market processes by which they could make profits and establish mechanisms for environmental self-regulation. The research uses elements from critical theory and eco-Marxist perspectives to shed light on the neoliberal framework in which these processes have taken place.